Flicker: Saving Refresh-Power in Mobile Devices through Critical Data Partitioning - Liu, Song; Pattabiraman, Karthik; Moscibroda, Thomas; Zorn, Ben (2009)
Mobile devices are left in sleep mode for long periods of time. But even while in sleep mode, the contents of DRAM memory need to be periodically refreshed, which consumes a significant fraction of power in mobile devices. This paper introduces Flicker, an application-level technique to reduce refresh power in DRAM memories. Flicker enables developers to specify critical and non-critical data in programs and the runtime system allocates this data in separate parts of memory. The portion of memory containing critical data is refreshed at the regular refresh-rate, while the portion containing non-critical data is refreshed at substantially lower rates. This saves energy at the cost of a modest increase in data corruption in the non-critical data. Flicker thus explores a novel and interesting trade-off between energy consumption and hardware correctness. We show that many mobile applications are naturally tolerant to errors in the non-critical data, and in the vast majority of cases, the errors have little or no impact on the application’s final outcome. We also find that Flicker can save between 20-25% of the power consumed by the memory subsystem in a mobile device, with negligible impact on application performance. Flicker is implemented almost entirely in software, and requires only modest changes to the application, operating system and hardware.